Action-angle variables for geodesic motions in Sasaki–Einstein spaces Yp, q. (15th January 2017) - Visinescu, Mihai
Abstract : We use action-angle variables to describe the geodesic motions in the 5-dimensional Sasaki–Einstein spaces Y p, q . This formulation allows us to study thoroughly the complete integrability of the system. We find that the Hamiltonian involves a reduced number of action variables. Therefore one of the fundamental frequencies is zero, indicating chaotic behavior when the system is perturbed.